Practical Guide to the NEC3 Professional Services Contract - Rowlinson, Michael (Hoboken : John Wiley & Sons, 2012)
Currently in its third edition, the NEC suite has become one of the UK & rsquo;s leading families of standard forms of contract for major construction and civil engineering projects. Part of the NEC suite, the Professional Services Contract (PSC) was drafted with the same process-based approach and objectives, offering a standard contract for the appointment of consultants providing professional services in an engineering or construction project. Embodying best practice in terms of project management, the basic philosophy of the PSC differs from the principles and approach of other standard cont.
6.6.1 Navigation tools6.6.2 Consultant remains responsible; 6.6.3 Ambiguities, discrepancies and impossibilities; 6.6.4 Prevention; 6.6.5 Law and interpretation; 6.7 Other matters: Practical issues; 6.7.1 Completing the Contract Data; 6.7.2 Prevention; 7 The Parties' Main Responsibilities; 7.1 Introduction; 7.2 The Employer's obligations; 7.3 The Consultant's obligations; 7.4 Other matters; 7.4.1 People; 7.4.2 Coordination; 7.5 Practical issues; 7.5.1 Importance of the Scope; 7.5.2 Forecasting the Time Charge; 7.5.3 The importance of key people.
7.5.4 Access to people, places and things not listed in the Contract Data.
Includes bibliographical references and index.
Print version record.
Keywords: NEC Contracts; NEC Contracts; NEC Contracts; Civil engineering contracts -- Great Britain; Architectural contracts -- Great Britain; LAW -- Military; Architectural contracts; Civil engineering contracts; Great Britain; Electronic books